Preserved Microvascular Endothelial Function in Young, Obese Adults with Functional Loss of Nitric Oxide Signaling - Harrell, John W.; Johansson, Rebecca E.; Evans, Trent D.; Sebranek, Joshua J.; Walker, Benjamin J.; Eldridge, Marlowe W.; Serlin, Ronald C.; Schrage, William G. (Frontiers in Physiology, 2015)
Data indicate endothelium-dependent dilation (EDD) may be preserved in the skeletal muscle microcirculation of young, obese adults. Preserved EDD might be mediated by compensatory mechanisms, impeding insight into preclinical vascular dysfunction. We aimed to determine the functional roles of nitric oxide synthase (NOS) and cyclooxygenase (COX) toward EDD in younger obese adults. We first hypothesized EDD would be preserved in young, obese adults. Further, we hypothesized a reduced contribution of NOS in young, obese adults would be replaced by increased COX signaling. Microvascular EDD was assessed with Doppler ultrasound and brachial artery infusion of acetylcholine (ACh) in younger (27±1 yr) obese (n=29) and lean (n=46) humans. Individual and combined contributions of NOS and COX were examined with intra-arterial infusions of L-NMMA and ketorolac, respectively. Vasodilation was quantified as an increase in forearm vascular conductance (ΔFVC). Arterial endothelial cell biopsies were analyzed for protein expression of endothelial nitric oxide synthase (eNOS). ΔFVC to ACh was similar between groups. After L-NMMA, ΔFVC to ACh was greater in obese adults (p<0.05). There were no group differences in ΔFVC to ACh with ketorolac. With combined NOS-COX inhibition, ΔFVC was greater in obese adults at the intermediate dose of ACh. Surprisingly, arterial endothelial cell eNOS and phosphorylated eNOS were similar between groups. Younger obese adults exhibit preserved EDD and eNOS expression despite functional dissociation of NOS-mediated vasodilation and similar COX signaling. Compensatory NOS- and COX-independent vasodilatory mechanisms conceal reduced NOS contributions in otherwise healthy obese adults early in life, which may contribute to vascular dysfunction.